2019
DOI: 10.1093/ofid/ofz434
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Fungal Marker β-D-Glucan After Antiretroviral Therapy and Association With Adiposity

Abstract: Background Bacterial translocation in HIV is associated with inflammation and metabolic complications; few data exist on the role of fungal translocation. Methods A5260s was a substudy of A5257, a prospective open label randomized trial in which treatment-naïve people with HIV (PWH) were randomized to tenofovir-emtricitabine (TDF/FTC) plus atazanavir-ritonavir (ATV/r), darunavir-ritonavir (DRV/r), or raltegravir (RAL) over 96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 39 publications
3
20
1
Order By: Relevance
“…11,26,[32][33][34][35][36] In the setting of HIV, higher blood BDG levels are associated with increased fat gain in ART-naïve PWH initiating treatment and with immune activation, increased systemic inflammation in ART-treated PWH and non-AIDS clinical events. 5, [16][17][18][19][20]37,38 Thus, there is a need to determine when best to measure markers of microbial translocation and gut damage in order to deliver accurate diagnostics and to assess treatment responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,26,[32][33][34][35][36] In the setting of HIV, higher blood BDG levels are associated with increased fat gain in ART-naïve PWH initiating treatment and with immune activation, increased systemic inflammation in ART-treated PWH and non-AIDS clinical events. 5, [16][17][18][19][20]37,38 Thus, there is a need to determine when best to measure markers of microbial translocation and gut damage in order to deliver accurate diagnostics and to assess treatment responses.…”
Section: Discussionmentioning
confidence: 99%
“…Certain contributors that give rise to fungal translocation include medical procedures such as surgery and haemodialysis, as well as conditions like liver cirrhosis, immune dysfunction, sepsis, intestinal hypoperfusion and persistent inflammation 11,26,32‐36 . In the setting of HIV, higher blood BDG levels are associated with increased fat gain in ART‐naïve PWH initiating treatment and with immune activation, increased systemic inflammation in ART‐treated PWH and non‐AIDS clinical events 5,16‐20,37,38 . Thus, there is a need to determine when best to measure markers of microbial translocation and gut damage in order to deliver accurate diagnostics and to assess treatment responses.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating BDG is currently used for the clinical diagnosis of Candida, Aspergillus, and Pneumocystis jirovecii invasive infections [33]. Recently, we and others have found that plasma levels of BDG are associated with epithelial gut damage and risk of developing inflammatory non-AIDS comorbidities in PLWH without invasive fungal infection (IFI) [24,25,28,29,[33][34][35][36]. We have also shown that plasma BDG levels are associated with reduced expression of Dectin-1 and NKp30 on monocytes and NK cells respectively, indicating direct cellular activation and inflammation by BDG.…”
Section: Introductionmentioning
confidence: 99%
“…first showed elevated plasma levels of BDG in PLWH in 2012 ( 19 ). Since then, several other groups including ours reported an association between BDG and epithelial gut damage, immune activation, inflammation, and risk of developing non-AIDS comorbidities ( 4 , 15 , 20 24 ). These findings suggest a significant role for BDG in chronic immune activation and the development of non-AIDS comorbidities in PLWH, although the mechanisms involved remain poorly understood.…”
Section: Introductionmentioning
confidence: 73%